Luminescence and ESR properties of Brazilian feldspars - Bitencourt, J. F. S.; Silva, D. M.; Silva, P. H.; Kinoshita, A.; Munita, C. S.; Tatumi, S. H. (Elsevier B.V., 2006)
The IRSL and TL responses of three different feldspar crystals have been analysed. TL measurements were taken in the ultraviolet UV (290-370 nm) and the visible VIS (340-610 nm) regions of the spectrum. For the UV region and for a natural sample, peaks were observed at 283, 287 and 310 degrees C for grey, white and pink crystals, respectively. For samples irradiated after prior preheating, it was noted that TL peaks occurred at about 200 degrees C for all the samples; irradiation with high doses above 500 Gy induced the formation of one additional peak at 170 degrees C. The VIS region results were similar to those for the UV. ESR experiments have been developed to verify the influence of radiation and heat treatments on the centres and preliminary results showed great variation in the intensities of [TiO(4)](-), Al-O(-)-Al and Fe(3+) centres. (c) 2006 Elsevier Ltd. All rights reserved.